The Reception and Critique of Hayden White’s Narrativistic-Tropological Project - Žemgulis, Vytautas (Problemos, 2004)
An American philosopher and historian of culture H. White is the most famous representative of narrativistic philosophy of history. In his capital work Metahistory (1973) he advanced the radical innovative narrativistic project of historical discourse based on tropology. The theory received a lot of comments among scholars of different branches and trends in humanities. In the first section of the article the initial version of H. White’s narrativistic-tropological project is presented. In the second section of the article the criticisms of this theory are reviewed, identifying main topics, discussing critics’ positions. In the third section of the article H. White’s reaction to criticism is discussed. In this discussion the author asks how these criticisms affected H. White’s conception, stimulating the elaboration of White’s late conception of figurative realism.